Validation and Reliability of Healthcare Workers’ Knowledge, Attitude, and Practice Instrument for Uncomplicated Malaria by Rasch Measurement Model - Ismail, Nahlah E.; Jimam, Nanloh S.; Dapar, Maxwell L. P.; Ahmad, Sohail (Frontiers in Pharmacology, 2020)
Background: This study assessed the validity and reliability of healthcare workers’ knowledge, attitudes, and practices instrument for uncomplicated malaria (HKAPIUM) for evaluation of healthcare workers’ knowledge, attitudes, and practices (KAP) on uncomplicated malaria management in primary healthcare (PHC) facilities in Plateau state, Nigeria. Methods: Relevant variables from literature, malaria treatment guidelines for Nigeria, and World Health Organization (WHO) were used to generate and present the items for the draft HKAPIUM scale, which was first screened by six experts before administered to 121 respondents who filled and returned immediately. The data were sorted and analyzed using Rasch measurement model (Bond & Fox software®). Results: The outcome of the initial screening showed high items content validity indices (I-CVI) (0.83–1.00) and high scale-CVI (S-CVI) {universal agreement (UA) within the experts (S-CVI/UA) (0.67–0.89) and the average CVI [S-CVI/Ave (0.94–0.98)]} for relevance, clarity, simplicity, and comprehensiveness. The Rasch analysis outputs showed good items’ reliability for the three factors (KAP) > 0.9 with high separation index values of > 2.0; however person reliability were poor (< 0.6) which were confirmed by their low separation values. Goodness of fit statistics indicated nine items not fitting the model based on the suggested fit index values of 0.6 to 1.5, and ± 2 for mean square (MNSQ) and standardized Z-score (Zstds) respectively, and 0.3 to 0.7 for “point-measure correlation coefficients” (PTMEA Corr). Deletion of misfit items resulted in the items and persons’ reliabilities falling above the minimum accepted limit of 0.6, with their separation values were all in the range of 1 and 2 which were acceptable. Similarly, fit index values for MNSQ infit and outfit, and Zstd parameters items in the new scale were all within the acceptable range of 0.6 to 1.5, and ±2 respectively, in addition to the positive PTMEA Corr as further confirmation of the items’ fitness to the model. Conclusion: The reduction of 27-items draft HKAPIUM scale to 18 items was successful with good reliability and fitness to the model.